Comparing the Effectiveness of Schema-Focused Couple Therapy and Emotion-Focused Couple Therapy on Marital Offense Forgiveness in Couples with Marital Discrepancies - Seidyousefi, Masoume; Mohamadian, Fathola; Nademi, Arash (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The aim of this study was to compare the effectiveness of schema-focused couple therapy and emotion-focused couple therapy on marital offense forgiveness in couples with marital discrepancies in Ilam city.Method: This was a quasi-experimental study with a pre-test, post-test, and follow-up design with a control group. The study population comprised 105 couples who sought counseling in Ilam during the second half of the year 2021. From this population, 30 couples were selected using a convenience sampling method and randomly assigned to three groups: emotion-focused intervention (10 couples), schema-focused intervention (10 couples), and a control group (10 couples). The emotion-focused group received Johnson's training package (2012) over 9 sessions, and the schema-focused group received the Young, Klosko, & Weishaar package (2003) also over 9 sessions. The control group did not receive any intervention. The research instrument used was the Marital Offense Forgiveness Scale by Paleari, Regalia, and Fincham (2009). Data were analyzed using repeated measures analysis of variance.Findings: Schema-focused couple therapy had a significant effect on marital offense forgiveness (F = 5.85, p = .025). Emotion-focused couple therapy also had a significant effect on marital offense forgiveness (F = 5.81, p = .045). These effects were reported to be stable at the follow-up stage. Additionally, there was no significant difference in the effectiveness of schema-focused couple therapy versus emotion-focused couple therapy on marital offense forgiveness.Conclusion: Both schema-focused and emotion-focused couple therapies are effective methods for enhancing marital offense forgiveness in couples with marital discrepancies.